Development of inducer-free expression plasmids using IPTG-inducible Pspac promoter for Bacillus subtilis - Chu, Phuong Thi Bich; Phan, Hanh Thi Thu; Nguyen, Hoang Duc; Phan, Trang Thi Phuong (Vietnam Journal of Science, Technology and Engineering, 2021)
An inducer-free expression vector for the low expression levels in Bacillus subtilis (B. subtilis) is necessary for fundamental research. In this study, we constructed inducer-free expression plasmids carrying Pspac, a well-known IPTG-inducible promoter, by removing a part of the lacI gene. Then, we analysed the expression of the target genes bgaB and gfp+ in B. subtilis. Western blot experiments demonstrated that the reporters from the inducer-free plasmids with Pspac could be produced at low levels in B. subtilis strains and were equivalent to their corresponding inducible constructs with 1 mM IPTG. The reporter activities showed that inducer-free expression from the Pspac promoter was dramatically less than that of the inducer-free plasmids with the strong promoters Pgrac01 and Pgrac100 reported previously, about 16.2 to 20.3 times for BgaB and 24.7 to 34.3 times for GFP+, respectively. In conclusion, the inducer-free expression vectors carrying Pspac promoters allow the constitutive expression of heterologous recombinant proteins at low levels in B. subtilis.